The Effect of Plasma on Bacteria and Normal Cells in Infected Wound. (30th November 2022) - Li, Yiqian; Nie, Lanlan; Jin, Shaohui; Sun, Chen; Lu, Xinpei
Abstract : Infected wound is one of the most common and serious problem in wound management. Cold atmospheric plasma (CAP) is considered to have a good effect in wound healing as a new type medicine. However, there is a key issue that has not been addressed in the treatment of infected wounds by plasma. Bacteria are always found in the deep region of the wound. When plasma is used to treat wounds, it also acts on normal tissue cells while decontaminating. What is the difference between the same dose of plasma acting on bacteria and normal cells? In this study, the most common bacteria (S. aureus, P. aeruginosa, and E. coli) in infected wound and two kinds of normal skin cells (human keratinocyte and human skin fibroblasts (HSF)) were selected to study the difference of the effects of the same dose of plasma on bacteria and cells. The results reveal that three kinds of 10 6 CFU mL bacteria could be effectively inactivated by 5 order after plasma treatment 3 min, and P. aeruginosa was more sensitive to plasma (could be inactivated 5 order after 2 min treatment). The 10 4  mL keratinocyte and HSF were treated with the same dose of plasma; keratinocyte can maintain over 90% of the activity and HSF cells can maintain over 70% of the activity. Moreover, the level of collagen I secreted by HSF increased. Therefore, cells can remain a high activity when a plasma dose capable of inactivating bacteria is applied to them.